1994
DOI: 10.1103/physrevb.49.4959
|View full text |Cite
|
Sign up to set email alerts
|

LEED structural analysis of Al(111)-K-(√3 × √3 )R30°: Identification of stable and metastable adsorption sites

Abstract: A detailed low energy electron diffraction analysis has been performed to investigate the adsorption of potassium on Al(111) at 90 K and at 300 K. At each temperature a (v 3 x~3)R30' structure is formed, however, the adsorbate positions are different. For adsorption at 90 K the adatoms occupy on-top sites and at 300 K they occupy substitutional sites, both geometries have hitherto been regarded as very unusual. An irreversible phase transition from the former to the latter stable structure occurs on warming to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Atoms, which are too big to fit into a bulk vacancy, can still prefer to take a substitutional site, because at the surface bigger atoms can simply sit somewhat above the center of the created surface vacancy. Since 1991 many examples of substitutional adsorption have been reported, as for example K on Al(111) Scheffler, 1992, 1993;Stampfl et al, 1992Stampfl et al, , 1994a, Na on Al(001) (Stampfl et al 1994b), Au on Ni(110) (Pleth Nielsen, 1993), Sb on Ag(111) (Oppo et al, 1993), Co on Cu(111) (Pedersen et al, 1997), Mn on Cu(001) (Rader et al, 1997), Co on Cu(001) (Nouvertné et al, 1999), to name a few. Thus, the phenomenon is not at all exotic, but rather general.…”
Section: Substitutional Adsorption and Formation Of Surface Alloysmentioning
confidence: 99%
“…Atoms, which are too big to fit into a bulk vacancy, can still prefer to take a substitutional site, because at the surface bigger atoms can simply sit somewhat above the center of the created surface vacancy. Since 1991 many examples of substitutional adsorption have been reported, as for example K on Al(111) Scheffler, 1992, 1993;Stampfl et al, 1992Stampfl et al, , 1994a, Na on Al(001) (Stampfl et al 1994b), Au on Ni(110) (Pleth Nielsen, 1993), Sb on Ag(111) (Oppo et al, 1993), Co on Cu(111) (Pedersen et al, 1997), Mn on Cu(001) (Rader et al, 1997), Co on Cu(001) (Nouvertné et al, 1999), to name a few. Thus, the phenomenon is not at all exotic, but rather general.…”
Section: Substitutional Adsorption and Formation Of Surface Alloysmentioning
confidence: 99%
“…[7,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], where it has been found that the majority of transition metal surfaces show a contraction of the first interlayer spacing, i.e., the spacing between the two outermost layers is smaller than in the bulk terminated (unrelaxed) surface. An expansion of the outermost interlayer spacing has been reported, e.g., for Mg(0 0 0 1) [29,33,37,44,45], Al(1 1 1) [11,22,24,28,31,46], and Pt(1 1 1) [21,22,47,50].…”
Section: Introductionmentioning
confidence: 98%
“…The atomic structure can be obtained with high accuracy using quantitative low-energy electron diffraction (LEED) intensity analysis [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. And theoretically, first-principles calculations also give an accurate description, see for example, Refs.…”
Section: Introductionmentioning
confidence: 99%
“…1-3,6,9,14 -16 For example, these calculations clearly showed that 1/3 monolayer of Na on Al͑111͒ prefers the substitutional site: At zero temperature the energy difference between substitutional and on-surface adsorption is 300 meV. For K the calculated adsorption energies for the substitutional and onsurface phase are almost degenerate, 2,6 indicating that the chemical nature of the adsorbate strongly affects the bonding. For Rb on Al͑111͒ first-principles calculations have not been reported so far.…”
Section: Introductionmentioning
confidence: 95%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Among these structures the ordered Al͑111͒-(ͱ3ϫͱ3)R30:X surface ͑with 1/3 monolayer of X ϭNa, K, Rb, Cs͒ probably has one of the simplest structures. Nevertheless, the system exhibits interesting structural phase transitions.…”
Section: Introductionmentioning
confidence: 99%